PERANCANGAN DESAIN KARAKTER DALAM BUKU ILUSTRASI INTERAKTIF ‘MENARI DENGAN MUANG SANGKAL’ UNTUK ANAK USIA 9-12 TAHUN - Maslahah, Safira Andini; Pungky Febi Arifianto; Mahimma Romadhona (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
Madura Island has many uniqueness, not only in terms of its famous beach tourism but also in terms of its culture. One of them is the muang sangkal dance which is the culture of Sumenep Regency. However, the muang sangkal dance is less popular among 9-12 year olds than other traditional dances. To solve this problem, an interactive illustration book "Dancing with Muang Sangkal" was designed which contains several main characters in it to introduce muang sangkal dance to children 9-12 years old. This research uses a qualitative method through observation, interviews, and FGD (Focus Group Discussion). Through this design, it is hoped that the target audience will be proud and know the existing nation's culture better.